Balloon dilation of stenotic nonvalved conduits after Fontan operation - Alehan, Dursun; Çeliker, Alpay; Ceviz, Naci (The Turkish Journal of Pediatrics, 1998)
The Fontan operation is used to supply a ventriculo-arterial connection in patients with tricuspid atresia. An important complication is the obstruction of the conduit that may necessitate reoperation. In these patients balloon dilation of the conduit stenosis has been advocated as a method to relieve the obstruction and postpone surgical replacement. While there are several reports about the balloon dilation of stenotic valved conduits, we do not have enough information about the results of balloon dilation of nonvalved conduits. We performed successful balloon dilations in two patients with tricuspid atresia who underwent the Fontan operation and had stenotic nonvalved conduits. In the first patient, the stenosis was relieved but recurred. A second balloon dilation procedure was performed, and the patient has been symptom free for one year. In the second patient, the stenosis was relieved but recurred. Our preliminary results suggest that balloon dilation is an efficient method to relieve the obstruction in stenotic nonvalved conduits and can be repeated successfully if the stenosis recurs.